Taxonomy and reproductive biology of the genus Zephyranthes Herb. (Liliaceae) in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2018)
The genus Zephyranthes Herb. is revised along with its pollination mechanism, seed germination and vegetative propagation. Detailed taxonomy of four Zephyranthes species occurring in Bangladesh, namely, Z. atamasco (L.) Herb., Z. candida (Lindl.) Herb., Z. carinata Herb. and Z. tubispatha (L’Her.) Herb. ex Traub. was studied with their updated nomenclature, important synonyms, phenology, specimens examined, habitat, distribution, economic value and mode of propagation. A dichotomous bracketed key is provided for easy identification of the species. Pollination investigation reveals that all studied species of Zephyranthes are self-pollinated. Minimum five days were required for germination of seeds in Z. atamasco, and three days each in Z. candida, Z. carinata and Z. tubispatha. Pseudovivipary type of germination has been reported in Z. candida and Z. carinata for the first time. The maximum number of seeds (30) per fruit are produced in Z. tubispatha, whereas the minimum seeds (2) per fruit are found in Z. atamasco. Vegetative propagation through bulb was found more suitable than seeds in Z. atamasco, Z. candida and Z. carinata. Pollen viability has been found 100% in Z. candida, and Z. tubispatha, whereas, Z. atamasco and Z. carinata have shown 80% and 98% viability, respectively. Bangladesh J. Plant Taxon. 25(1): 57-69, 2018 (June)